Integrative taxonomy supports the existence of two distinct species within Hypsiboas crepitans (Anura: Hylidae) (2017)
ABSTRACT: The Neotropical treefrog Hypsiboas crepitans (Wied, 1824) has an intriguing disjunct geographic distribution encompassing two large patches: the Atlantic Forest in southeastern South America and from the Guiana Shield to Central America in the north, that are separated by more than 1500 km. This distribution pattern led us to review the available material and re-examine, under an integrative approach, the taxonomic status of these populations. We assessed data using three lines of evidence: morphology, morphometry, and mitochondrial DNA. All of them suggest that the populations from the two geographical ranges are not conspecific. Given that the type material of H. crepitans is from the State of Bahia, Brazil, and that specimens from this area cluster with the southeastern group, we resurrect Hypsiboas xerophyllus (Duméril & Bibron, 1841) for the populations of the northwestern group. Hyla levaillantii Duméril & Bibron, 1841, Hyla doumercii Duméril & Bibron, 1841, Hyla fuentei Goin & Goin, 1968, and Hypsiboas indris Cope, 1867 are synonymized with H. xerophyllus.